Urban futures: representations of South Asian cities in recent SF literature - Harder, Hans (Nidān, 2025)
In the light of accelerated urbanization processes in South Asia since the 19th century, particularly after Independence and into the present, it is hardly surprising that the city is becoming an ever more prominent topos of literary representation. Science Fiction (SF), an area of speculative fiction that has solidly established itself in various literary cultures of the subcontinent, is especially prone to such orientations, and all signs are set for the trend to continue. After some general remarks about the advent and development of South Asian SF and reflections on urbanity in 20th-century writings in the genre, I turn to contemporary SF and portray some examples of 21st century texts and the futures they envisage for a number of South Asian cities: Dhaka, Kolkata, Delhi, Trichy, Chennai and Mumbai. In the conclusion, I argue that two dystopian turns—the first mid-20th century and roughly coinciding with Independence, the second end-20th century and connected with globalizing crisis scenarios—can be deduced from the material and used for contextualizing the productions within a global imaginaire of the future.